2021
DOI: 10.1186/s12879-021-06917-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with bronchiectasis with nontuberculous mycobacterial disease in Mainland China: a single center cross-sectional study

Abstract: Background The diagnosis and treatment of patients with bronchiectasis and nontuberculous mycobacterium (NTM) pulmonary disease are challenging issues and the treatment is also prolonged and depends on the species. There is limited information on patients with bronchiectasis and NTM pulmonary disease in Mainland China. Methods This cross-sectional study was conducted at the China–Japan Friendship Hospital, Beijing, China. Those adult patients who m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Similarly, the association of lower BMI with NTM pulmonary infection has been previously reported [ 11 , 12 , 19 , 21 ]. While lower BMI may simply be a result of the NTM infection itself, it has been suggested that decreased fat mass with corresponding regulatory dysfunction of adipokines that participate in the immune response, such as leptin and adiponectin, may increase susceptibility to NTM infection [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Similarly, the association of lower BMI with NTM pulmonary infection has been previously reported [ 11 , 12 , 19 , 21 ]. While lower BMI may simply be a result of the NTM infection itself, it has been suggested that decreased fat mass with corresponding regulatory dysfunction of adipokines that participate in the immune response, such as leptin and adiponectin, may increase susceptibility to NTM infection [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 64%
“…Patients with NTM pulmonary infection are generally characterized by older age [ 11 13 , 19 ] which may entail an age-dependent decrease in respiratory muscle strength and mucocilliary clearance and an association with other factors such as impaired cell-mediated immunity, cytokine production, and phagocytosis [ 20 ]. The pathophysiologic mechanisms underlying the association of NTM infection and female gender, also reported by others [ 11 , 12 , 21 ], are not fully understood. It is noteworthy that there is a similar gender bias of bronchiectasis in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently sufficient literature describing the radiological features of NTM. Some features such as thin-walled cavity and bronchiectasis ( 21 , 22 ) in the middle lobes and the left upper lobe are typical NTM imaging features, as are other such as consolidation, GGO, nodules and “tree-in-bud” pattern and so on ( 9 ). However, SOP due to NTM is combined with imaging changes in areas such as near the periphery of LL, and “reversed halo sign” ( 23 ), especially during NTM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is characterized by recurrent cough, sputum production, and respiratory tract infections (1)(2)(3). Bacterial infections trigger an inflammatory response, which further exacerbates airway inflammation and airway structural damage, leading to the well-described "vicious cycle" of bronchiectasis (4,5).…”
Section: Introductionmentioning
confidence: 99%